STUDY OF IRAQI TAX PERFORMANCE SINCE FROM (1995-2010) - محمد علي, عماد; ثامر, لقاء فنجان (Journal of Economics and Administrative Sciences, 2013)
The existence of the tax Coupled with the existence of the power of the political   Sociality and the evolution of its concept differes according to the concept of the role of the state and its evolution in the economical life and  it represents on of the main sources of funding one hand and an effective means that enables the state to intervene in various aspects of the economic life on the other hand. Tax also can be considered as a tool used to re-distribue the in class. Perhaps Iraq suffers from and in the marginalization to the role of taxes in funding and in turn the adoption of the Iraqi budget on oil revenues to finance the aspects of expenitvre which can pose a risk on the total Iraqi economy because of the linkage of the oil  prices with the foreign monetary system and it is influenced by it, which makes Iraq's economy depends on a single supplier to receive its revenue and thus it can be subject to the fluctuations that could take place in the international arena especially since  Iraq was exposed to irregular conditions resulted from the economic blockade and the events of 2003 and the subsequent changes follow.   For the purpose of  facilating  the task of the study,It is divided into two periods. The first one was between  1995-2002,and the second one was represented between 2003-2010 and the researcher too. into consideration the knowledge of taxes and the indicatoes of tax performauce which were represented by the tax capacity, tax burden, And tax enderavos and then presenting some procedures which participate in attaining the success of tax system and making it more effective. The researcher reached some conclusions and recomemandations which was the most impostant one of them the hard circumstances that Iraq suffered during the period of study(1995-2010) that had its economical, social and political effects on Iraq which influcnce negatively on the gains of the tax and on the efficiency of the tax performance in iraq.   The most important  recommendation . was since the Iraqi economic enjoyed an  increase in its natural resources but it was one-sided sector which made it suffering from the fluctuations and crises so it must allempt to reduce the dependence of the Iraqi budget on the revenues of oil and trying to diverse its revenuse through the increase of tax incomes and activating them because the oil is not lasting resource and we must keep it to the coming generations.